SUGAR-seq reveals the transcriptome and N-linked glycosylation landscape of mononuclear phagocytes at single-cell resolution in a mouse model of autosomal dominant osteopetrosis type 2 - Yu Sha; Lingyu Huang; Lei Zhang; Xianliang Hou; Chune Mo; Cuiping Pan; Gengshuo Chen; Sha Luo; Minglin Ou (BMC Biology)
Abstract Background Heterozygous mutation of CLCN7 (R286W) is commonly found in patients with benign autosomal dominant osteopetrosis. However, there is no evidence from animal models to confirm that it is a disease mutation. And the characteristics of the bone marrow cell (BMC) landscape in osteopetrosis at the single-cell level are completely unknown till now. Results In this study, we generated the first autosomal dominant osteopetrosis type 2 (ADO2) mouse model with typical phenotypes carried a mutation Clcn7 (r284w) corresponding to CLCN7 (R286W) observed in human patients using gene editing technology. And then, we conducted the first-ever single-cell analysis of the RNA expression and N-linked glycosylation profiles for the mouse BMCs by SUrface-protein Glycan And RNA-sequencing (SUGAR-seq). We identified 14 distinct cell types and similar proportion of neutrophils in both ADO2 and wild type mice, confirmed by flow cytometry analysis. The N-linked glycosylation modifications of BMCs were significantly downregulated detecting by SUGAR-seq, which was similar to the situation of N-Glycan profiling by the 4D Label-Free N-Glycosylation Proteomics Analysis. Particularly noteworthy is the heterogeneity of classic monocytes. We identified six cell subtypes, but only two cell subtypes were found with different proportion of cell, whose different expressed genes were associated with NF-κB-inducing kinase / Nuclear Factor-kappa B (NIK/NF-κB) signaling and other pathway associated with osteoclast differentiation. Conclusions Our murine model confirms that the human CLCN7 (R286W) is a pathogenic mutation for ADO2. Additionally, our single-cell analyses reveal the heterogeneity of monocytes in ADO2, and the abnormal glycosylation modifications across various subtypes may represent important events in the pathogenesis of osteopetrosis.